Factors Influencing Solid Waste Segregation Behavior of People in Bangkok - Bejranonda, Somskaow; Lim, Aunkung (Journal of Applied Economics and Management Strategy, 2025)
This research aims to study the factors influencing solid waste segregation behavior among residents living in Bangkok. The study collected data through an online questionnaire from a sample group of 421 individuals aged 15 and above, residing in Bangkok, during May–June 2024. The research applied the Theory of Planned Behavior (TPB) and used descriptive statistics, which include mean, percentage, and tables, along with quantitative statistics by using structural equation model in the form of path analysis. Most respondents were female, aged 34 years in the average, holding Bachelor degree, working as employee of the private company to earn average personal income of 29,482 baht per month and have average current spending of 17,530 baht per month. The average number of earning family members was 3. They had great knowledge of waste sorting and viewed that household waste has caused the environmental problems. They had intention to perform solid waste segregation. The findings revealed that the factors influencing solid waste segregation behavior among the sample group include: 1) Direct factors: Residence area, age, gender, prior participation in environmental activities, level of intention, attitude towards the behavior, conformity to reference groups, perceived behavioral control, and denial of responsibility for waste segregation; 2) Indirect factors: Economic motivation, moral norms, knowledge of waste types and the environment, indirect attitude, indirect conformity to reference groups, and education level; and 3) Factors with both direct and indirect effects: Indirect perceived behavioral control. Therefore, policy makers should promote the sorting of all types of solid waste through various media channels or through individuals that the people trust, and should also eliminate the cost barriers related to waste sorting.